Pengembangan Potensi Kepariwisataan Berbasis Masyarakat di Desa Pengkol, Kabupaten Sukoharjo, Jawa Tengah - Tular Sudarmadi (Bakti Budaya: Jurnal Pengabdian kepada Masyarakat, 2018)
Administratively, Pengkol Village is listed in Sub-district Pengkol, Nguter District, Sukoharjo Regency, Central Java. While this village is not categorized as a poor village, income earned from wet-feld rice farming and fshing in Colo dam is not sufcient to support villagers’ daily life. It is not surprising that most of the productive age population prefer to work in factory or as labor migrants in Singapore, Malaysia, Hong Kong and Saudi Arabia. A glimpse, of natural resources, cultural heritage and everyday life shows that Desa Pengkol can be managed as a Tourism Village Attraction. Tis article delineates the way in which Pengkol village is developed, managed, and empowered by short, middle and long community service program of the Community Based Tourism. Focusing on identifcation of tourism object attraction, this preliminary -short program- makes an eﬀort to improve, not only the economic, social, and cultural, but also the villagers day to day life welfare. Given such eﬀorts the Pengkol villagers are expected to stay during their productive age in their village as the owner and manager of tourism village attraction business. Further, they will not work as an industry worker or labor migrants.